2016
DOI: 10.1038/srep39354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrothermal pretreatment on the structural changes of alkaline ethanol lignin from wheat straw

Abstract: Due to the enormous abundance of lignin and its unique aromatic nature, lignin has great potential for the production of industrially useful fuels, chemicals, and materials. However, the rigid and compact structure of the plant cell walls significantly blocks the separation of lignin. In this study, wheat straw was hydrothermally pretreated at different temperatures (120–200 °C) followed by post-treatment with 70% ethanol containing 1% NaOH to improve the isolation of lignin. Results demonstrated that the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 39 publications
(44 reference statements)
4
46
0
Order By: Relevance
“…Thus, as expected, the structure of lignin is affected by temperature, which is a finding previously reported (see e.g. Chen et al 24 ). In this sense, 150 ∘ C and ethyl lactate-enriched solutions could be preferred as organosolv operating conditions for those interested in the exploitation of remnant sugars in the solid waste instead of lignin recovery.…”
Section: Resultssupporting
confidence: 89%
“…Thus, as expected, the structure of lignin is affected by temperature, which is a finding previously reported (see e.g. Chen et al 24 ). In this sense, 150 ∘ C and ethyl lactate-enriched solutions could be preferred as organosolv operating conditions for those interested in the exploitation of remnant sugars in the solid waste instead of lignin recovery.…”
Section: Resultssupporting
confidence: 89%
“…The relatively high intensity of the 1320 cm −1 peak compared with the 1270 cm −1 peak, as well as the strong intensity of the band at 1123 cm −1 , which is also typical for syringyl units and is attributed to aromatic C−H in‐plane bending, are in accordance with the expected high ratio of syringyl over guaiacyl units in hardwood native lignins . Furthermore, the intensity of these bands is similar amongst the lignins isolated from the 190 and 220 °C treated biomass samples, although partial demethoxylation of alkaline ethanol lignin from wheat straw at severe hydrothermal conditions has been previously reported …”
Section: Resultssupporting
confidence: 75%
“…This indicates that severe hydrothermal pretreatment conditions favor the formation of carbonyl groups in the isolated lignin. This has been attributed to the cleavage of β‐O‐4′ linkages of the native lignins and the formation of Hibbert ketones under severe pretreatment conditions . The bands at 1607, 1510, 1460, and 1427 cm −1 are assigned to the skeletal vibrations of the aromatic ring.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al. combined hydrothermal pretreatment and alkaline ethanol extraction to remove lignin from wheat straw, and observed that β−O−4, β−β′, and β−5 linkages, as well as aliphatic OH in lignin, showed a tendency of being broken, but phenolic OH increased steadily with increasing temperature . It was noted that some hydrogen bonds and ether linkages between lignin and cellulose/or hemicellulose, as well as those in lignin, were broken during the process.…”
Section: Introductionmentioning
confidence: 99%